Social exclusion monitor bulletin (December 2012) - Azpitarte, Francisco (My University, 2012)
In this third bulletin we summarise the results of the social exclusion monitor, recently updated using 2010 data, and investigate the persistence of social exclusion.
Social Exclusion Monitor Bulletins
Keywords: Disadvantage -- Exclusion; Employment; Health; Income & Finance -- Poverty and disadvantage; Education and Training; Health and wellbeing; Income, wealth and finances; Labour market; Employment; Income & Finance; Disadvantage; Health; Education and Training; Exclusion; Poverty and disadvantage; Employment and unemployment; Health and wellbeing; Income, wealth and finances